Towards Deeper Financial Integration in Europe: What the Banking Union Can Contribute - Claudia M. Buch; Tobias Körner; Benjamin Weigert (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2013)
The agreement to establish a Single Supervisory Mechanism in Europe is a major step towards a Banking Union, consisting of centralized powers for the supervision of banks, the restructuring and resolution of distressed banks, and a common deposit insurance system. In this paper, we argue that the Banking Union is a necessary complement to the common currency and the Internal Market for capital. However, due care needs to be taken that steps towards a Banking Union are taken in the right sequence and that liability and control remain at the same level throughout. The following elements are important. First, establishing a Single Supervisory Mechanism under the roof of the ECB and within the framework of the current EU treaties does not ensure a sufficient degree of independence of supervision and monetary policy. Second, a European institution for the restructuring and resolution of banks should be established and equipped with sufficient powers. Third, a fiscal backstop for bank restructuring is needed. The ESM can play a role but additional fiscal burden sharing agreements are needed. Direct recapitalization of banks through the ESM should not be possible until legacy assets on banks' balance sheets have been cleaned up. Fourth, introducing European-wide deposit insurance in the current situation would entail the mutualisation of legacy assets, thus contributing to moral hazard.
urn:nbn:de:gbv:3:2-23714
Keywords: E02; E42; G18; 330; banking union; Europe; single supervisory mechanism; risk sharing